Simulation Study on Oil Film Bearing Capacity of Wet Clutch Friction Disk at Initial Separation State - Yuan Yuelan; Zhang Fenglian; Ma Biao (Jixie chuandong, 2017)
To study the oil film bearing capacity of wet clutch friction disk at initial separation state,the bearing capacity model at fixed friction gap is built. Using finite element method,the oil film pressure distribution in a friction pair is calculated,and comparative analysis with the oil film bearing capacity of radial groove friction components and non-groove ones is performed. Through simulation calculation of the oil bearing capacity of different friction disk structural parameters,the effect of groove depth,number and proportion on oil film bearing capacity is studied. The reasonable structural parameters are obtained to improve the bearing capacity of oil film as theoretical basis for the structure design of friction disk.